Coconut Oil Salve from Gamal Tree Leaves (Gliricidia sepium) as an Alternative Treatment for Lumpy Skin Disease (LSD) in Cattle - Setiawati, Euis Nia; Hasanudin, Aang; Armelia, Vony (International Journal of Environment, Agriculture and Biotechnology, 2024)
Lumpy Skin Disease (LSD) is an infectious skin disease caused by the Lumpy Skin Disease Virus (LSDV), posing a significant threat to cattle and buffalo farming. This research aims to determine the effectiveness of a salve made from gamal tree (Gliricidia sepium) leaves and coconut oil for the treatment of LSD in cattle. The study is divided into two parts: 1) the production of Gamal Leaf Oil Salve (SMDG), involving the collection of gamal leaves and the creation of a salve by mixing gamal leaves with coconut oil; and 2) the application of SMDG to cattle exposed to LSD with three concentrations: 1) 50%: 500 grams of gamal leaves in 1 liter of coconut oil (SMDG 50%); 2) 75%: 750 grams of gamal leaves in 1 liter of coconut oil (SMDG 75%); 3) 100%: 1000 grams of gamal leaves in 1 liter of coconut oil (SMDG 100%). The data were analyzed using Kruskal-Wallis, and significant differences among treatments were further analyzed using Mann-Whitney comparisons. The results of the study indicate that the application of Gamal Leaf Oil Salve (SMDG) with a concentration of 100% resulted in the highest recovery compared to concentrations of 75% and 50% for cattle exposed to LSD. Nodules began to flatten, and ulcers started to dry on the seventh day (Day 7), where in Experiments S2 and S3, the results were relatively similar with sizes ranging from 1 to 1.5 cm, which was better than in S1 where nodule size was 1.5 to 2 cm. A concentration of 100% SMDG is safe for use as a botanical antiviral and can reduce nodule size and dry ulcers in the treatment of Lumpy Skin Disease (LSD) after 14 days of application.